2015
DOI: 10.1371/journal.pone.0117484
|View full text |Cite
|
Sign up to set email alerts
|

PyNTTTTGT and CpG Immunostimulatory Oligonucleotides: Effect on Granulocyte/Monocyte Colony-Stimulating Factor (GM-CSF) Secretion by Human CD56+ (NK and NKT) Cells

Abstract: CD56+ cells have been recognized as being involved in bridging the innate and acquired immune systems. Herein, we assessed the effect of two major classes of immunostimulatory oligonucleotides (ODNs), PyNTTTTGT and CpG, on CD56+ cells. Incubation of human peripheral blood mononuclear cells (hPBMC) with some of these ODNs led to secretion of significant amounts of interferon gamma (IFN-γ), tumor necrosis factor alpha (TNF-α) and granulocyte/monocyte colony-stimulating factor (GM-CSF), but only if interleukin 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Interestingly, human NK cells produce GM-CSF after IL2 treatment and TLR9 signaling or Candida albicans infection. [17][18][19] However, high levels of interferon and tumor necrosis factor were also detected under these stimulatory conditions, leading to an activating phenotype that does not coincide with the phenotype displayed by U-NKs during alloBMT settings. To further demonstrate the GM-CSF-dependent hematopoietic role of U-NKs, neutralizing antibodies to GM-CSF were used during cocultures and indeed prevented alloBMC growth ( Figure 2C).…”
Section: Org Frommentioning
confidence: 99%
“…Interestingly, human NK cells produce GM-CSF after IL2 treatment and TLR9 signaling or Candida albicans infection. [17][18][19] However, high levels of interferon and tumor necrosis factor were also detected under these stimulatory conditions, leading to an activating phenotype that does not coincide with the phenotype displayed by U-NKs during alloBMT settings. To further demonstrate the GM-CSF-dependent hematopoietic role of U-NKs, neutralizing antibodies to GM-CSF were used during cocultures and indeed prevented alloBMC growth ( Figure 2C).…”
Section: Org Frommentioning
confidence: 99%
“…CpG and PyNTTTTGT ODNs have a number of common characteristics but also remarkable differences (41). Among the latter: 1) PyNTTTTGT ODNs do not induce IFN␣ secretion (13), 2) they stimulate granulocyte-macrophage colonystimulating factor (GM-CSF) secretion in human CD56ϩ (NK/ NKT) cells (42), and 3) they stimulate in vivo and in vitro MSCs proliferation (22). Interestingly, IMT504 stimulated CD56ϩ NKT cells that have been postulated to convey peripheral tolerance and protection against autoimmune diabetes (30).…”
mentioning
confidence: 99%
“…On day 5, the cells were analyzed by FACS and the expression of CD1a was evaluated as a marker of DC differentiation. DCs were then incubated in the presence of 10 µg/ml CpG2006 and IMT504 (Rodriguez et al 2015) (kindly donated by Dr Alejandro Montaner, Instituto Milsten, CONICET, Argentina), R848 or both for 24 h. DCs were then processed to assess the expression of HLA-DR and CD86 (BD Biosciences) by flow cytometry as described above. The generation of human DCs has been approved by the Ethical Committee of the Academia Nacional de Medicina (Buenos Aires, Argentina, CEIANM 76/2015).…”
Section: Generation Of Human Dcsmentioning
confidence: 99%
“…7c). We evaluated the effect of human TLR9 agonists CpG2006 and IMT504 (Rodriguez et al 2015), TLR7/8 agonist R848 and their combination on the expression of coactivation markers in human DCs. We found that while both TLR9 agonists did not significantly stimulate HLA-DR (Fig.…”
Section: Evaluation Of Tlr9 and Tlr7 Agonists In Human Dcsmentioning
confidence: 99%